You Are Not the Father: The Need to Terminate the Parental Rights of Rapists to Protect Victims and Children. (21st June 2021) - O'Dea, Christina
Abstract : Twenty‐seven of fifty states require a criminal conviction to terminate the parental rights of a rapist. If a rape results in pregnancy and a woman chooses to carry that pregnancy to term, she may be subjected to fight her rapist in court over the parental rights of the child. In 2015, Congress passed the Rape Survivor Child Custody Act to incentivize states to lower this standard to "clear and convincing evidence." This Note proposes that this Act be adopted by all fifty states to universally lower the standard of proof required in these cases. Key Points for the Family Court Community: States that follow the incentive of the Rape Survivor Child Custody Act guide the courts to place importance on the victim and their child, not the rapist. States that follow the incentive of the Rape Survivor Child Custody Act allow a woman to raise a healthy child without negatively impacting her parental abilities. States that do not follow the incentive of the Rape Survivor Child Custody Act force women to have continued interaction with their rapist, resulting in traumatic psychological effects on the survivor. States that do not follow the incentive of the Rape Survivor Child Custody Act allow rapists to use the threat of pursuing parental rights to coerce survivors into not prosecuting rape.